Justice and democracy : cross-cultural perspectives - Bontekoe, Ronald, 1954-; Stepani͡ant͡s, M. T. (Mariėtta Tigranovna) (University of Hawai'i Press, 1997)
Today democracy is increasingly recognized around the world as the only form of government with moral legitimacy. The problems of establishing and preserving truly democratic institutions, however, vary dramatically from culture to culture. Justice and Democracy explores these problems from a wide range of perspectives, theoretical and practical. It addresses problems relating to the distortion of democratic decision-making by the gross disparities in wealth that arise in capitalist economies, and, in particular, focuses on the problems relating to the reconciliation of democratic values with the indigenous religious and social values of a culture.